Transcriptome Analysis of Genes Associated with the Artemisinin Biosynthesis by Jasmonic Acid Treatment under the Light in Artemisia annua - Hao, Xiaolong; Zhong, Yijun; Fu, Xueqing; Lv, Zongyou; Shen, Qian; Yan, Tingxiang; Shi, Pu; Ma, Yanan; Chen, Minghui; Lv, Xueying; Wu, Zhangkuanyu; Zhao, Jingya; et al. (Frontiers in Plant Science, 2017)
Abstract Artemisinin is a sesquiterpene lactone endoperoxide extracted from a traditional Chinese medicinal plant Artemisia annua. Artemisinin-based combination therapies (ACTs) are recommended as the best treatment of malaria by the World Health Organization (WHO). Both the phytohormone jasmonic acid (JA) and light promote artemisinin biosynthesis in A. annua. Interestingly, we found that the increase of artemisinin biosynthesis by JA was dependent on light. However, the relationship between the two signal pathways mediated by JA and light remains unclear. Here, we collected the A. annua seedlings of 24 h continuous light (Light), 24 h dark treatment (Dark), 4 h MeJA treatment under the continuous light conditions (Light-MeJA-4h) and 4 h MeJA treatment under the dark conditions (Dark-MeJA-4h) and performed the transcriptome sequencing using Illumina HiSeq 4000 System. A total of 266.7 million clean data were produced and assembled into 185,653 unigenes, with an average length of 537 bp. Among them, 59,490 unigenes were annotated and classified based on the public information. Differential expression analyses were performed between Light and Dark, Light and Light-MeJA-4h, Dark and Dark-MeJA-4h, Light-MeJA-4h and Dark-MeJA-4h, respectively. Furthermore, transcription factor (TF) analysis revealed that 1588 TFs were identified and divided into 55 TF families, with 284 TFs down-regulated in the Dark relative to Light and 96 TFs up-regulated in the Light-MeJA-4h relative to Light. 8 TFs were selected as candidates for regulating the artemisinin biosynthesis and one of them was validated to be involved in artemisinin transcriptional regulation by Dual-Luciferase (Dual-LUC) assay. The transcriptome data shown in our study offered a comprehensive transcriptional expression pattern influenced by the MeJA and light in A. annua seedling, which will serve as a valuable resource for further studies on transcriptional regulation mechanisms underlying artemisinin biosynthesis.